Shenqi Yanshen Formula (SQYSF) protects against chronic kidney disease by modulating gut microbiota. Issue 3 (1st March 2022) - Zhang, Ling; Zhang, Tai-Jun; Li, Ying; Xiong, Wei-Jian
ABSTRACT: In this study, we make an elucidation toward both the therapeutic effect and the mechanism of Shenqi Yanshen Formula (SQYSF) to chronic kidney disease (CKD). CKD mouse model was established and achieved in a way of adenine (200 mg/kg) perfusion. Six weeks later, those mice in the model group were fed with SQYSF (3.60 g/kg/day) every day (the captopril group was given 12.5 mg/kg/day by gavage every day, and control group and the model group were both given the gavage of equal volumes of normal saline); 4 weeks after the administration, we had our detection to physiological indicators of mice, performed ELISA assay to detect inflammatory factor expressions, then assay of 16S sequencing was used to reveal the difference of intestinal flora. Our results showed that after SQYSF treatment, both the expressions of serum creatinine (Scr) and blood urea nitrogen (BUN) came with a significant decline, indicating the outstanding performances of SQYSF in alleviating impairment in renal function and elevating mice's physiological function. SQYSF significantly reduced the degree of renal fibrosis in CKD mice, and remarkably down-regulated the expressions of toll-like receptor 5 (TLR5), nuclear factor-kappaB (NF-κb), p65, tumor necrosis factor (TNF)-α, interleukin (IL)-1β and IL-6. Additionally, SQYSF has more than ability in significantly changing the composition in mice's intestinal flora, but also in greatly increasing the abundance of Succinivibrionaceae and Aeromonadales in the mouse intestine. This study clarified the therapeutic effect of SQYSF on CKD and regulation of inflammatory factors and intestinal flora, and provided new ideas for treatment on CKD.